2021
DOI: 10.1111/are.15100
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein requirement of white shrimp, Penaeus vannamei (Boone, 1931) juveniles, reared in inland ground water of medium salinity

Abstract: A 60‐day feeding trial was conducted to evaluate the effect of dietary protein level on growth, digestive enzymes and haemato‐biochemical responses of Penaeus vannamei juveniles in inland ground saline water (IGSW) of 15 ppt salinity. The acclimated shrimp (avge. wt., 4.03 ± 0.05 g) were randomly distributed into seven groups, viz. TCP20, TCP25, TCP30, TCP35, TCP40, TCP45 and TCP50, in triplicate with the stocking density of 15 shrimp per tank (275 L). Seven semi‐purified hetero‐nitrogenous (200–500 g crude pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 139 publications
(138 reference statements)
1
10
0
Order By: Relevance
“…This is attributed to the similar concentration of K + ions in the rearing water after fortification with potash. In support of our findings, Hurtado et al (2007) and Jana et al (2021) also documented that dietary lipid or protein or the ambient water salinity did not influence the Na + /K + ‐ATPase enzyme activities in the gill of shrimp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is attributed to the similar concentration of K + ions in the rearing water after fortification with potash. In support of our findings, Hurtado et al (2007) and Jana et al (2021) also documented that dietary lipid or protein or the ambient water salinity did not influence the Na + /K + ‐ATPase enzyme activities in the gill of shrimp.…”
Section: Discussionsupporting
confidence: 91%
“…From these eight shrimps carefully hepatopancreas (weight was recorded for calculation of HPSI) and intestine were dissected out and quickly homogenized (5% homogenate) in iced phosphate buffer solution (pH 7.4) for assay of digestive enzymes. Gills were homogenized (10% homogenate) in iced SEI buffer (pH 7.3) using an automated homogenizer (Miccra, D9, Remi India) under iced conditions (Jana et al, 2021; Saraswathy et al, 2021) for Na + /K + ‐ATPase assay. The tissue homogenates were then centrifuged at 7000 g for 15 min in a refrigerated centrifuge, and the aliquot supernatant was collected in sample vials.…”
Section: Methodsmentioning
confidence: 99%
“…If there is no benefit feeding higher concentrations of crude protein, this potentially results in improved economic efficiency. Several studies have demonstrated that shrimp experience better growth performance and lower FCR when fed higher protein diets (Xia et al, 2010;Shahkar et al, 2014;Jana et al, 2021); however, daily exchanges of water occurred in these studies. In contrast, other researchers reported that there is the possibility of reducing dietary crude protein concentration in shrimp feed without affecting growth performance when BFT is applied Panigrahi et al, 2019).…”
Section: Shrimp Growthmentioning
confidence: 91%
“…But, in compared to brackish and marine water, inland ground saline water (IGSW) is deficient of potassium ion with high calcium ions and variable concentrations of magnesium ions (Allan et al, 2001), which affect the physiological homeostasis and growth performance of fish (Aklakur, 2017). However, several countries have successfully cultured different euryhaline species in IGSW with or without fortification of potassium ions (Jana et al, 2006;Partridge and Lymbery, 2008;Jana et al, 2021a). Thus, genetically improved farmed tilapia (GIFT) could be the most suitable species for culturing in IGSW because of its high growth rate, disease resistance and tolerance to wide range of salinity and ionic variation.…”
Section: Introductionmentioning
confidence: 99%